2008
DOI: 10.3390/s8042886
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated MEMS Gyroscope Array with Higher Accuracy Output

Abstract: Abstract:In this paper, an integrated MEMS gyroscope array method composed of two levels of optimal filtering was designed to improve the accuracy of gyroscopes. In the firstlevel filtering, several identical gyroscopes were combined through Kalman filtering into a single effective device, whose performance could surpass that of any individual sensor. The key of the performance improving lies in the optimal estimation of the random noise sources such as rate random walk and angular random walk for compensating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…The simulation results showed that the gyroscopes with drifts of 8.66 °/h could be reduced to a virtual gyroscope with a drift of 0.062 °/h when the component gyroscopes are assumed to have a correlation factor of −0.33329. Another two-level optimal filtering method for fusing three gyroscopes was presented by Honglong Chang in [5]. It achieved higher accuracy than individual gyroscope but the continuous-time Kalman filter was not solved to reveal the system property.…”
Section: Open Accessmentioning
confidence: 99%
“…The simulation results showed that the gyroscopes with drifts of 8.66 °/h could be reduced to a virtual gyroscope with a drift of 0.062 °/h when the component gyroscopes are assumed to have a correlation factor of −0.33329. Another two-level optimal filtering method for fusing three gyroscopes was presented by Honglong Chang in [5]. It achieved higher accuracy than individual gyroscope but the continuous-time Kalman filter was not solved to reveal the system property.…”
Section: Open Accessmentioning
confidence: 99%
“…The quality of these devices has big impacts in overall performance of the inertial sensor system (Honglong, Liang, Wei, Guangmin, & Weizheng, 2008). This technology provides good accuracy and reliability, it is not conducive to a MEMS-based AHRS due to its larger size and greater power requirements.…”
Section: Inertial Measurement Unitmentioning
confidence: 99%
“…2) Separation the inconsistent properties over space. It would be nice, if we can use some other similar gyroscope [4][5][6]. Then we would have two equations and two variables.…”
Section: The Resolution Of the Physical Contradictionmentioning
confidence: 99%
“…Additional "source" of the information about motion can be some other sensor as it is recommended in [4][5][6].…”
Section: B the Analysis Of The Problem 1)mentioning
confidence: 99%